Diabetes and severity of COVID-19: What is the link?. (October 2020) - Pitocco, D.; Viti, L.; Tartaglione, L.; Di Leo, M.; Rizzo, G.E.; Manto, A.; Rizzi, A.; Caputo, S.; Pontecorvi, A.
Abstract: In Diabetes Mellitus the loss of capacity to regulate immunity, the reduction of pulmonary functions and the pro-thrombotic state determine the severity of COVID-19.